Penerapan Latihan Range Of Motion (ROM) Pasif Terhadap Perubahan Kekuatan Otot Ekstremitas Pada Pasien Lansia Dengan Kasus Stroke Di Rumah Sakit Umum Daerah (RSUD) Dr. Soediran Mangun Sumarso Wonogiri - Melinia Nira Natasya; Erika Dewi Nooratri (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Stroke is a health problem that we often encounter in today's modern society, stroke is a very serious disease phenomenon in Indonesia and throughout the world. Stroke is a condition where the blood supply to the brain is disrupted due to a blockage or rupture. blood vessels of a person with various symptoms such as hemiparesis, slurred speech, loss of balance and decreased muscle strength and difficulty walking. Stroke is one of the causes of decreased muscle strength where muscle strength is a contraction in the striated muscle fibers (voluntary muscles) that lasts briefly and each contraction occurs on a single stimulus from the nerve. Objective: to determine the results of applying passive Range of Motion (ROM) exercises to increasing muscle strength in the Neuro Center ward of RSUD DR. Soediran Mangun Sumarso Wonogiri. Method: the application of this journal uses a qualitative description method. Results: the results after the implementation was an increase in muscle strength in both respondents. Conclusion: there is an increase in muscle strength in both respondents, Range of Motion (ROM) Exercise therapy can increase muscle strength in stroke sufferers.